Maps, Land, and Power Politics: Realizing a Folk Pagan Vision of Landscape - Kotlik, George (International journal for the study of new religions, 2023)
This study considers five "maps" produced by the Asatru Folk Assembly (AFA) to demonstrate that AFA maps communicate power. AFA maps communicate power in several ways. First, they signal AFA community-building efforts. Second, they centralize the importance of AFA property/hofs and Folk Pagans themselves in a Folk Pagan perspective/worldview. A societal crisis or destabilization accentuates the language the maps communicate, especially with regard to power relations and a neo-medieval future. In this way, AFA hofs are administrative centers for AFA members residing within their district territory that also function as Folk Pagan community centers and places of importance where decisions of significance are made for in-group Folk Pagans. By reorienting a mainstream perspective/worldview toward an AFA Pagan perspective/worldview, observers are able to better understand the language AFA maps employ to communicate the importance of AFA property/places/spaces. This is especially the case in relation to existing United States federal and state-level power structures, given that the AFA is, to whatever degree, a millenarian and prepper/prepper-like community/organization that is mindful of an impending Ragnarök, or apocalypse. AFA Pagans realize their conceptualized notions of the world by putting such conceptions onto their maps. In doing so, AFA Pagans communicate an AFA Pagan worldview characterized by millenarianism and a focus on subcultural AFA Pagan power and power relations divorced from mainstream society.